Elastomer preparation method and flexible electronic device

By covalently cross-linking relaxor ferroelectric polymers and cross-linking agents, elastomers with high dielectric constants are prepared, solving the problems of high dielectric loss and limited dielectric constant in existing technologies, and realizing flexible electronic devices with high dielectric constants and good elasticity.

CN120829611APending Publication Date: 2025-10-24NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410483376.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-22
Publication Date
2025-10-24

AI Technical Summary

Technical Problem

Existing high dielectric constant elastomers suffer from problems such as high dielectric loss, limited dielectric constant, and insufficient elasticity during the preparation process.

Method used

Using a relaxor ferroelectric polymer as the matrix, an elastomer with a high dielectric constant is prepared by covalent cross-linking with a cross-linking agent, such as polyethylene oxide diamine. The cross-linking temperature and time are controlled at 188–268℃ for 0.5–1.5 h. After forming the basic elastomer, it is further processed in a vacuum oven.

Benefits of technology

It achieves a high dielectric constant increase in elastomers, with a 230% increase in room temperature dielectric constant and an elastic recovery rate greater than 80% at 75% strain, making it suitable for energy storage, electric card refrigeration, and electro-actuated applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120829611A_ABST
    Figure CN120829611A_ABST
Patent Text Reader

Abstract

The invention provides an elastomer preparation method and a flexible electronic device, and the preparation method comprises the steps: selecting a relaxation ferroelectric polymer as a matrix of an elastomer, the dielectric temperature spectrum of the relaxation ferroelectric polymer being greater than 20 DEG C; and carrying out covalent cross-linking treatment on the relaxation ferroelectric polymer and a preset cross-linking agent to obtain the elastomer. The rebound resilience and dielectric constant of the elastomer can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of flexible electronic preparation process, more specifically, to a flexible film and a flexible electronic device. BACKGROUND

[0002] Currently, high dielectric constant dielectric materials are essential components in modern electronic devices, such as non-volatile memory devices, energy storage devices and circuits, and high dielectric constant elastomers are key materials for sensors, information storage and electro-driven devices in wearable electronic devices. Similar to the idea of functional material elasticity, there are usually two methods to develop high dielectric constant elastomers: adding high dielectric constant materials to elastomers, or exploring the intrinsic elasticity of polymeric dielectric materials with high dielectric constant. It can be seen that no matter which method is chosen, the key factor is the material with high dielectric constant, such as ferroelectric polymers and fillers.

[0003] Generally speaking, dielectric materials can be divided into two categories: organic and inorganic. Inorganic dielectric materials, such as ferroelectric ceramics, are prone to breakage. On the other hand, organic dielectric materials are mainly composed of ferroelectric small molecules, molecular ferroelectrics and ferroelectric polymers, which are suitable for flexible electronic devices. Molecular ferroelectrics, synthesized by "ferroelectric chemistry" method, have excellent electromechanical coupling coefficient and piezoelectric coupling coefficient, but due to their small molecular structure, they lack large ductility under strain, like inorganic materials. Ferroelectric polymers, such as polyvinylidene fluoride (PVDF), as a plastic polymer material, have good mechanical properties, but their dielectric constant is relatively low, usually in the range of 8-18. However, as a linear semi-crystalline polymer, PVDF tends to undergo plastic deformation rather than elastic deformation under large strain. No matter which way we choose to prepare high dielectric constant elastomers, exploring the elasticity of polymer ferroelectrics to achieve intrinsic elastomers with high dielectric constant is a promising way.

[0004] Currently, the main method to prepare elastomers with high dielectric constant is to add inorganic or conductive fillers to the elastomers. However, the composite elastomers prepared by adding fillers usually have some unavoidable shortcomings. For example, mixing ferroelectric ceramic fillers into elastomers fails to achieve significant improvement in dielectric constant at low filler concentration, while at higher concentration it is easy to cause electrical breakdown, loss of flexibility and separation of fillers from the elastomer matrix caused by electrostrictive strain. In the case of using conductive fillers, the dielectric constant of the composite material will increase due to the percolation phenomenon. However, once the percolation threshold of the conductive filler is reached, the composite material will undergo a transition from insulator to conductor, thus causing extremely high dielectric loss.

[0005] Therefore, it is necessary to explore a preparation method to improve the dielectric constant of the elastomer while minimizing dielectric loss and meeting the elasticity requirements. SUMMARY

[0006] In view of the above problems, the present application provides an elastomer preparation method and a flexible electronic device to solve the problems of insufficient material resilience, low dielectric constant of the elastomer, etc.

[0007] The elastomer preparation method provided by the present application comprises selecting a relaxor ferroelectric polymer as the matrix of the elastomer, wherein the temperature spectrum of the relaxor ferroelectric polymer is greater than 20℃; and covalently crosslinking the relaxor ferroelectric polymer with a predetermined crosslinking agent to obtain the elastomer.

[0008] In addition, the relaxor ferroelectric polymer is P(VDF-TrFE-CFE), and the ratio of P(VDF-TrFE-CFE) is (50-70):(25-30):(6-10).

[0009] In addition, the crosslinking agent is polyethylene oxide diamine PEG-diamine with a molecular weight of 1000; and during the crosslinking process, the mass ratio of the relaxor ferroelectric polymer to the polyethylene oxide diamine is 50:1-50:10.

[0010] In addition, the crosslinking includes chemical crosslinking, photo-crosslinking, and thermal crosslinking.

[0011] In addition, the process of covalently crosslinking the relaxor ferroelectric polymer with the predetermined crosslinking agent comprises: configuring a uniform mixed solution of the relaxor ferroelectric polymer and the crosslinking agent; performing spin coating or casting operation on the mixed solution, and air drying after spin coating or casting to form a basic elastomer; and performing thermal crosslinking on the air-dried basic elastomer, wherein the crosslinking temperature is 188-268℃, and the crosslinking reaction time is 0.5h-1.5h.

[0012] In addition, the process of configuring a uniform mixed solution of the relaxor ferroelectric polymer and the crosslinking agent comprises: dissolving the relaxor ferroelectric polymer and the crosslinking agent into a uniform mixed solution using cyclohexanone or DMF.

[0013] In addition, the mixed solution is uniformly spread on a predetermined substrate and naturally air dried at room temperature; the air-dried mixed solution is placed in a vacuum oven at a temperature of 50℃ for 6h to form a basic elastomer; and the basic elastomer after drying is placed in a vacuum oven at a temperature of 240℃ for 1h to finally form the elastomer.

[0014] Further, an optional technical solution is that 150 mg of relaxor ferroelectric polymer is dissolved in 15 mg of polyethylene oxide diamine in 1 mL of cyclohexanone, and oscillated in a vortex oscillator for 12 h to form a mixed solution; the mixed solution is cast on a glass plate and air dried at room temperature for 12 h, and dried in a vacuum oven at a temperature of 50°C for 6 h to form a base elastomer; the dried base elastomer is dried in a vacuum oven at 240°C for 1 h to form the elastomer; after the glass sheet is soaked in deionized water for 1 h, the elastomer is separated from the glass sheet.

[0015] Further, an optional technical solution is that the crosslinking agent includes at least one of a peroxide, an amino compound, a polysulfide phenol compound, and a polyphenol compound.

[0016] In another aspect, the present application also provides a flexible electronic device including a flexible film prepared by the elastomer preparation method described above.

[0017] By using the elastomer preparation method and the flexible electronic device described above, a relaxor ferroelectric polymer is selected as a base of the elastomer, the relaxor ferroelectric polymer has a dielectric spectrum greater than 20°C, and the elastomer with an intrinsic high node constant is obtained by covalent crosslinking treatment of the relaxor ferroelectric polymer and a predetermined crosslinking agent, in addition, the ferroelectric property and the piezoelectric property of the elastomer are also affected.

[0018] To the accomplishment of the foregoing and related ends, one or more aspects of the application comprise the features hereinafter fully described. The following description and the annexed drawings set forth in detail certain illustrative aspects of the application. These aspects are indicative, however, of but a few of the various ways in which the principles of the application can be employed. Other aspects and advantages of the application will become apparent from the following detailed description, taken in conjunction with the accompanying drawings, illustrating by way of example the principles of the application. BRIEF DESCRIPTION OF DRAWINGS

[0019] Other objects and results of the application will become more fully understood and appreciated only upon consideration of the following detailed description, taken in conjunction with the accompanying drawings. In the drawings:

[0020] Figure 1 A flow chart of the elastomer preparation method according to the embodiment of the present application;

[0021] Figure 2 A crosslinking reaction formula according to the embodiment of the present application.

[0022] Figure 3 A stress-strain curve of the elastomer according to the embodiment of the present application;

[0023] Figure 4 A hysteresis loop diagram of the elastomer according to the embodiment of the present application;

[0024] Figure 5 Stress strain curves of different crosslinking density films according to embodiments of the application.

[0025] The same reference numbers in all the figures indicate similar or corresponding features or functions. DETAILED DESCRIPTION

[0026] In the following description, for the purposes of explanation, numerous specific details are set forth in order to provide a thorough understanding of one or more embodiments. It can be apparent, however, that such embodiments can be practiced without these specific details. In other instances, well-known structures and devices are shown in block diagram form in order to facilitate describing one or more embodiments.

[0027] In the description of the present application, it needs to be understood that the terms "center", "longitudinal", "transverse", "length", "width", "thickness", "upper", "lower", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate the orientation or positional relationship based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, and therefore cannot be understood as indicating or implying that the devices or elements referred to must have a particular orientation, be constructed and operated in a particular orientation, and therefore cannot be understood as limiting the present application.

[0028] To solve the problems of high dielectric loss and limited dielectric constant in the preparation of existing elastomers, the present application provides an elastomer preparation method and a flexible electronic device, a relaxor ferroelectric polymer is selected as the matrix of the elastomer, the dielectric temperature spectrum of the relaxor ferroelectric polymer is greater than 20℃, the elastomer with intrinsic high node constant is obtained by covalent crosslinking treatment of the relaxor ferroelectric polymer and the preset crosslinking agent, in addition, the ferroelectric performance and piezoelectric performance of the elastomer are also affected.

[0029] To describe the elastomer preparation method and the flexible electronic device of the present application in detail, the specific embodiments of the present application will be described in detail below in combination with the drawings.

[0030] Figure 1 A schematic flowchart of the elastomer preparation method according to an embodiment of the present application is shown.

[0031] As shown in Figure 1 , the elastomer preparation method of the present application embodiment comprises:

[0032] S100: a relaxor ferroelectric polymer is selected as the matrix of the elastomer, the dielectric temperature spectrum of the relaxor ferroelectric polymer is greater than 20℃;

[0033] S200: covalently crosslinking the relaxor ferroelectric polymer with a preset crosslinking agent to obtain a final target elastomer.

[0034] The elastomer is prepared by covalently crosslinking the relaxor ferroelectric polymer with the crosslinking agent, and the base for preparing the elastomer can be selected from P(VDF-TrFE-CFE), and the ratio of P(VDF-TrFE-CFE) is (50-70):(25-30):(6-10) mol%, preferably 64.6:26.2:9.2 mol%.

[0035] As a specific example, the crosslinking agent can be polyethylene oxide diamine PEG-diamine with a molecular weight of 1000; during the covalent crosslinking process, the mass ratio of the relaxor ferroelectric polymer to the polyethylene oxide diamine is in the range of 50:1-50:10, and the covalent crosslinking includes but is not limited to chemical crosslinking, photo-crosslinking and thermal crosslinking.

[0036] In addition, the crosslinking agent can include at least one of peroxide, amino compound, polysulfide phenol compound, and polyphenol compound, and can be flexibly set according to the preparation requirements of the elastomer.

[0037] Specifically, during the covalent crosslinking process, a uniform mixed solution of the relaxor ferroelectric polymer and the crosslinking agent is first configured; then, the mixed solution is spin-coated or flow-coated, and then air-dried after spin-coating or flow-coating to form a basic elastomer; finally, the basic elastomer after air-drying is heat-crosslinked, the crosslinking temperature is 188-268℃, and the crosslinking reaction time is 0.5h-1.5h.

[0038] In the configuration process of the above mixed solution, cyclohexanone or DMF can be used to dissolve the relaxor ferroelectric polymer and the crosslinking agent into a uniform mixed solution.

[0039] In a specific embodiment of the present application, the mixed solution is first uniformly spread on a preset substrate and naturally air-dried at room temperature; then, the mixed solution after air-drying is placed in a vacuum oven at a temperature of 50℃ for 6h to form a basic elastomer; finally, the basic elastomer after drying is placed in a vacuum oven at 240℃ for 1h to form an elastomer.

[0040] It can be seen that by adjusting the ratio of the relaxor ferroelectric polymer to the crosslinking agent or the molecular weight of the crosslinking agent, the crosslinking density of the two can be adjusted, so as to control the mechanical and electrical properties of the elastomer.

[0041] Specifically, 150 mg of relaxor ferroelectric polymer and 15 mg of polyethylene oxide diamine can be dissolved in 1 mL of cyclohexanone to form a mixed solution by oscillating in a vortex oscillator for 12 hours; the mixed solution is cast on a glass plate and air-dried at room temperature for 12 hours, and then dried in a vacuum oven at a temperature of 50 DEG C for 6 hours to form a base elastomer; the dried base elastomer is dried in a vacuum oven at 240 DEG C for 1 hour to form an elastomer; the glass sheet is soaked in deionized water for 1 hour, and then the elastomer is separated from the glass sheet to obtain the final patterned elastomer.

[0042] It can be known that the elastomer of the embodiment of the present application realizes the elastification of the ternary PVDF copolymer with high dielectric constant at room temperature through cross-linking, the ferroelectric performance and piezoelectric performance of the obtained thin film elastomer are not affected, and the increase of the dielectric constant at room temperature is realized, which is increased by 230% compared with the uncross-linked thin film. The elastomer of the present application has an intrinsic high dielectric constant, the elastic recovery rate thereof is greater than 80% under a strain of 75%, and the dielectric constant thereof can reach 54.2 at 25 DEG C and 100 Hz, so that the elastomer is superior to ordinary ferroelectric elastomers in the fields of energy storage, electric refrigeration and electric driving.

[0043] It should be noted that the cross-linking reaction mechanism of P(VDF-TrFE-CFE) and PEG-diamine in the embodiment of the present application is a nucleophilic substitution reaction, which mainly includes three steps: first, the polymer is removed HF to form a main chain double bond under alkaline conditions; then, the diamine cross-linking agent acts as a nucleophile and adds to the double bond to generate an unstable intermediate product; finally, the cross-linking point eliminates HF to generate an imine bond, and the cross-linking reaction is completed. The reaction equation of the cross-linking reaction is shown in Figure 2 .

[0044] wherein, the calculation method of the cross-linking density is as follows: the cross-linking density p is set as the fraction of cross-linking point v to repeating unit N0, that is, p=v / N0=(x+y) / (m+n+h), wherein x, y, m, n and h respectively represent the repeating units of P(VDF-TrFE-CFE). Assuming that the added PEG-diamine cross-linking agent completely reacts with the polymer, one molecule of PEG-diamine has two molecules of cross-linking point, the cross-linking point is twice the number of cross-linking agent molecules, if the molecular weight of PEG-diamine is 1000; the average molecular weight of P(VDF-TrFE-CFE) (64.6 / 26.2 / 9.2) is 70.24 (70.24=0.646*64.03+0.262*82.02+0.092*80.45), and the mass ratio of PEG-diamine to P(VDF-TrFE-CFE) is a:b, then the cross-linking density p=2(a / 1000) / (b / 70.24).

[0045] In addition, in the preparation of the elastomer of the present application, the intrinsic high dielectric constant elastomer can be prepared into different morphologies according to the use requirements in different scenarios, such as a thin film prepared by using a flow casting method or a spin coating method, a granular shape prepared by using an extrusion molding process, a block shape prepared by using injection molding or compression molding, and a hydrogel formed by swelling in a solution.

[0046] The preparation method of the elastomer of the present application will be described in detail below in combination with specific examples.

[0047] In the following examples, the polymer matrix P(VDF-TrFE-CFE) (64.6:26.2:9.2 mol%) is a solid white powder, the crosslinking agent PEG-diamine is a solid white powder with a molecular weight of 1000 g / mol, cyclohexanone has a purity of 99.5%, and N,N-dimethylformamide (DMF) has a purity of 99.5%.

[0048] Example One

[0049] 1. In a glass sample bottle, 150 mg of P(VDF-TrFE-CFE) and 15 mg of PEG-diamine were dissolved in 1 mL of cyclohexanone, and the crosslinking density was 1.40%, and then the mixture was shaken in a vortex shaker for 12 h to ensure uniform mixing;

[0050] 2. The mixed solution was cast on a glass plate with a size of 2.5 cm x 2.5 cm, air dried at room temperature for 12 h, and then dried in a vacuum oven at 50°C for 6 h, and then crosslinked at 240°C for 1 h;

[0051] 3. After soaking the glass sheet in deionized water for 1 h, the thin film can be completely separated from the glass sheet, and an elastic film (i.e., an elastomer) is obtained.

[0052] Figure 3 A stress-strain curve of the elastomer according to Example 1 of the present application is shown.

[0053] By Figure 3 It can be seen that when the thin film with a crosslinking density of 1.40% of the elastomer is stretched to 1.75 times the original length, the thin film still maintains an elastic recovery rate of more than 80%, and the thin film has good resilience.

[0054] Figure 4 A hysteresis loop diagram of the elastomer according to Example 1 of the present application is shown.

[0055] As Figure 4 shown, the thin film with a crosslinking density of 1.40% of the elastomer still maintains the characteristics of a ferroelectric, and the crosslinking treatment does not cause the thin film to lose ferroelectricity.

[0056] Example Two

[0057] The mass ratio of P(VDF-TrFE-CFE) to PEG-diamine is changed to 100:2, and other preparation processes are described in the embodiment one, and the cross-linking density in this embodiment is 0.28%.

[0058] Embodiment three

[0059] The mass ratio of P(VDF-TrFE-CFE) to PEG-diamine is changed to 100:5, and other preparation processes are described in the embodiment one, and the cross-linking density in this embodiment is 0.70%.

[0060] Embodiment four

[0061] The mass ratio of P(VDF-TrFE-CFE) to PEG-diamine is changed to 100:15, and other preparation processes are described in the embodiment one, and the cross-linking density in this embodiment is 2.11%.

[0062] Embodiment five

[0063] The mass ratio of P(VDF-TrFE-CFE) to PEG-diamine is changed to 100:20, and other preparation processes are described in the embodiment one, and the cross-linking density in this embodiment is 2.81%.

[0064] In summary, as shown in the stress-strain curve of the film with different cross-linking densities, with the increase of the cross-linking density, the crystallinity is continuously reduced, the elongation at break is gradually reduced, the modulus is gradually reduced, and the yield phenomenon is also gradually disappeared, indicating that the film has completed the transition from plasticity to elasticity. Figure 5

[0065] Corresponding to the above-mentioned elastomer preparation method, the application also provides a flexible electronic device comprising a flexible film prepared by the above-mentioned elastomer preparation method.

[0066] It should be noted that the above-mentioned embodiment of the flexible electronic device can refer to the description in the embodiment of the elastomer preparation method, which will not be repeated here.

[0067] According to the above-mentioned elastomer preparation method and flexible electronic device of the application, the relaxor ferroelectric polymer is selected as the matrix of the elastomer, the dielectric spectrum of the relaxor ferroelectric polymer is greater than 20℃, the relaxor ferroelectric polymer is covalently cross-linked with the predetermined cross-linking agent to obtain the elastomer with intrinsic high node constant, in addition, the ferroelectric property and piezoelectric property of the elastomer are also affected, and high resilience and high dielectric constant can be realized at the same time.

[0068] ​The elastomer preparation method and the flexible electronic device according to the present application are described above with reference to the drawings by way of example. However, it should be understood by those skilled in the art that various modifications can be made to the above-mentioned elastomer preparation method and the flexible electronic device according to the present application without departing from the content of the present application. Therefore, the scope of protection of the present application should be determined by the content of the appended claims.

Claims

1. A method of preparing an elastomer, characterized by, The application relates to a flexible film and a preparation method thereof. The preparation method comprises the following steps: selecting a relaxor ferroelectric polymer as a matrix of an elastomer, wherein the relaxor ferroelectric polymer has a dielectric temperature spectrum greater than 20 DEG C; and covalently crosslinking the relaxor ferroelectric polymer with a preset crosslinking agent to obtain the elastomer.

2. The preparation method of the elastomer according to claim 1, wherein the relaxor ferroelectric polymer is P(VDF-TrFE-CFE), and the proportion of the P(VDF-TrFE-CFE) is (50-70):(25-30):(6-10) mol%.

3. The preparation method of the elastomer according to claim 1, wherein the crosslinking agent is polyethylene glycol diamine PEG-diamine with a molecular weight of 1000.

4. The preparation method of the elastomer according to claim 1, wherein the crosslinking comprises chemical crosslinking, photo crosslinking and thermal crosslinking. The process of covalently crosslinking the relaxor ferroelectric polymer with the preset crosslinking agent comprises the following steps: preparing a uniform mixed solution of the relaxor ferroelectric polymer and the crosslinking agent; performing spin coating or flow casting on the mixed solution, and then air drying after the spin coating or flow casting to form a basic elastomer; and performing thermal crosslinking on the air-dried basic elastomer, wherein the crosslinking temperature is 188-268 DEG C, and the crosslinking reaction time is 0.5-1.5 h. The process of preparing the uniform mixed solution of the relaxor ferroelectric polymer and the crosslinking agent comprises the following steps: dissolving the relaxor ferroelectric polymer and the crosslinking agent into a uniform mixed solution by using cyclohexanone or DMF.

7. The preparation method of the elastomer according to claim 6, wherein the mixed solution is uniformly spread on a preset substrate, and then naturally air dried at room temperature; the air-dried mixed solution is placed in a vacuum oven at a temperature of 50 DEG C for drying for 6 h to form a basic elastomer; and the dried basic elastomer is placed in a vacuum oven at a temperature of 240 DEG C for drying for 1 h to finally form the elastomer.

8. The preparation method of the elastomer according to claim 6, wherein 150 mg of the relaxor ferroelectric polymer and 15 mg of polyethylene glycol diamine are dissolved in 1 mL of cyclohexanone, and then oscillated in a vortex oscillator for 12 h to form a mixed solution; the mixed solution is flow casted on a glass plate, and then air dried at room temperature for 12 h, and then dried in a vacuum oven at a temperature of 50 DEG C for 6 h to form a basic elastomer; the dried basic elastomer is placed in a vacuum oven at a temperature of 240 DEG C for drying for 1 h to form the elastomer; and the glass plate is soaked in deionized water for 1 h, and then the elastomer is separated from the glass plate.

9. The preparation method of the elastomer according to claim 6, wherein the crosslinking agent comprises at least one of peroxide, an amino compound, a polysulfide phenol compound and a polyphenol compound.

5. The method of claim 4, wherein the elastomer is prepared by a process comprising: The application further discloses a flexible film prepared by the preparation method of the elastomer. ​ ​ ​ 6. The method of claim 5, wherein the elastomer is prepared by a process comprising: ​ ​ ​ ​ ​ ​ ​ ​ ​ ​ ​ ​ ​ 10. A flexible electronic device, characterized by ​

Citation Information

Cited By

  • Ferroelectric polymer and method for preparing ferroelectric polymer through crosslinking modification

    CN121270771A